2022
DOI: 10.1038/s41598-022-24714-4
|View full text |Cite
|
Sign up to set email alerts
|

Lodging resistance of rice plants studied from the perspective of culm mechanical properties, carbon framework, free volume, and chemical composition

Abstract: In this study, four varieties of rice were cultivated on the same farmland under same conditions and for same duration. However, their lodging resistance was found to be obviously different from each other. Herein, three key factors that highly influenced the lodging resistance were identified. First, in terms of morphological trait, in contrast to the generally believed theory that the overall thickness of the fresh culm wall governs the strength, the thickness of the depressed region of the dried basal culm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Several recent studies on the association between culm height and lodging resistance in rice have been published, where they observed that culm length was positively correlated to lodging resistance, implying that taller plants with longer culms were more resistant to lodging due to their greater culm diameter and strength [66]. Meanwhile, the flexibility of the culm would be more significant than its rigidity for the rice plants' lodging resistance [67]. The obtained results also revealed a favourable proportion between culm height and plant height in paddy, where a plant hormone known as brassinosteroid is essential in the regulation of plant height [68].…”
Section: Effects Of Heavy Metals On Rice Growthmentioning
confidence: 99%
“…Several recent studies on the association between culm height and lodging resistance in rice have been published, where they observed that culm length was positively correlated to lodging resistance, implying that taller plants with longer culms were more resistant to lodging due to their greater culm diameter and strength [66]. Meanwhile, the flexibility of the culm would be more significant than its rigidity for the rice plants' lodging resistance [67]. The obtained results also revealed a favourable proportion between culm height and plant height in paddy, where a plant hormone known as brassinosteroid is essential in the regulation of plant height [68].…”
Section: Effects Of Heavy Metals On Rice Growthmentioning
confidence: 99%
“…The culm and leaf sheaths form the basal of the rice plant, which is composed of the mechanical tissue layers, and vascular bundles that play dominant roles in the lodging resistance of rice plants (Liu et al 2022). Based on the data 4 landraces (Ale hendik, Hare nona portu, Hare mean 21, and Hare mean 22) are expected to have weak lodging resistance, 5 landraces (Hare metan, Ale kukefuhu, Hare R-oitu, Hare metan 8, and Ale isu puti) medium lodging resistance, and the other 14 landraces (Hare metama, Hare R-sinco, Mean morin, Fos mean, Ale hendik, Hare mean 11, Ale mamea ula lesa, Hare claán, Hare mean 14, Hare belit, Resa silaun, Ale mamea, Ale kalaha dikar, and Hare nacroma) strong lodging resistance.…”
Section: Agro-morphological Characterizationmentioning
confidence: 99%